Changes in Chinese-Indonesian Identity: Indonesianization or Re- Sinicization? - Harryanto Aryodiguno (AEGIS : Journal of International Relations, 2018)
During the Suharto era, which began after the anti-Chinese riots in 1965 as a result of the deterioration of the relation between Indonesia and China, forced policies of assimilation was adopted for curtailing the Chinese culture and to control Chinese-Indonesians. Yet, anti-Chinese sentiments remained, and attacks against them reached its climax in May 1998, when anti-Chinese riots recurred because of the allegation that Chinese-Indonesians had an advantageous economic status, and they were the culprit that brought financial crisis to Indonesia. The May 1998 riot ended Suharto’s era, and Chinese Indonesians saw improvement in their position and condition. Now, they strive to find their own identity and political status. Their efforts to do so were also influence by the rise of China. That is why, this paper aims at examining whether the reintroduction of Chinese cultural celebrations into Chinese-Indonesian community would result in the demise of policies of assimilation. It also examines whether the rise of China would propel them to establish a closer identification with the People’s Republic of China. How do Chinese-Indonesians view their identity? How do they choose this identity and their political inclinations? These are the research questions this paper is going to answer. The findings show that the status of the Chinese in Indonesia is divided into two groups. The first group is the one who is determined to break away from Chinese identification, and the second group is the one that still maintains their Chinese culture.